VD_FINDINFO 106/2011/FAB vom 25. Juli 2011 - VD Tribunal cantonal (2011)
PROROGATION DE FOR, CONSORITÉ, STIPULATION POUR AUTRUI, CLAUSE D'ARCHITECTE, COMPÉTENCE RATIONE LOCI | 112 al. 2 CO, 112 CO, 56 CPC, 7 LFors, 9 LFors